Implementation of Multicultural and Inclusive Education: Challenges and Good Practices in Early Childhood Education - Anadya Nurul Yustikarini; Hajerah Hajerah; Ananda Sahira Jasmin; Julita Julita; Nurul Izzah Hazirah; Sandrina Nabihah (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
This study highlights the critical importance of instilling mutual respect, tolerance, and acceptance of differences from an early age through multicultural and inclusive education, addressing current challenges in early childhood education (ECE) centers. Conducted at Tweety, Uminda, and Ar-Rohman Kindergartens—selected for their varying levels of student diversity and distinct inclusive approaches—the research aimed to identify student diversity, evaluate inclusive education implementation, and examine the roles of teachers and parents in fostering a supportive learning environment. Employing a case study method, data were collected through observations, questionnaires, and interviews with school principals, teachers, and parents. Findings reveal that students possess diverse backgrounds in religion, culture, habits, character, and learning abilities. To address this, schools actively promote multicultural values through daily routine activities, such as collaborative play, group work, sharing, mutual assistance, and non-discriminatory respect. Teachers further support this by providing individualized guidance tailored to each child’s unique needs, ensuring comfortable participation for all. Furthermore, parents play a vital role by cooperating with the schools and cultivating an attitude of respect for differences within the home environment. Despite these positive efforts, challenges remain, notably managing the varied characters and abilities of the children and the ongoing need for enhanced communication between schools and parents. Ultimately, the study concludes that implementing multicultural and inclusive education in ECE centers is highly effective. It successfully equips young children with positive social attitudes and the essential ability to interact harmoniously within diverse environments from an early age.